Infected or not: are PCR-positive oropharyngeal swabs indicative of low pathogenic influenza A virus infection in the respiratory tract of Mallard Anas platyrhynchos? - Wille, Michelle (BioMed Central, 2014)
Detection of influenza virus in oropharyngeal swabs collected during wild bird surveillance is assumed to represent respiratory infection, although intestine is the main site of infection. We tested this assumption by histological examination of the respiratory tract of wild Mallards with virus-positive oropharyngeal swabs. Thirty-two of 125 Mallards tested had viral-RNA positive oropharyngeal swabs. The respiratory tracts of four Mallards with the most virus were examined in detail by immunohistochemistry. None had detectable virus antigen in the respiratory tract, suggesting it was not infected. An alternative explanation is that the oropharynx was contaminated with virus through feeding in surface water or through preening.